Kleopatra i Dydona-antyteza ideału kobiety czasów Augusta - Dorota Dutkiewicz (In Gremium. Studies in History, Culture and Politics, 2009)
Cleopatra and Dido as an antithesis of Roman woman's ideal in the time of AugustusThe ideal of a Roman woman differed substantially from the mythical image of Dido the queen of Carthage as well as the conduct of Cleopatra the queen of Egypt. Both Vergil and Plutarch describing Dido or Cleopatra did not criticize directly the women lifestyles. Nonetheless, they did emphasize in their derailed descriptions their improper behavior which for the reader of that time was explicitły blameworthy. The criticism of the characters was not expressed directły - it was a deliberate intention of the writers. Skilfully Ied by the author, the reader was able to draw the  'right' concłusions as he was going deeply into the literary work. Furthermore, by comparing the description of Dido and Aeneas by Vergil with the description of Cleopatra and her lovers by Plutarch, one may notice some similarities which are not accidental.